The association of the marker of cardiovascular RISK – QTc interval with 64V/64I CCR2 gene polymorphism and metabolic syndrome components In the general male population of Novosibirsk - A. A. Kuznetsov; M. I. Voevoda; V. N. Maksimov; I. V. Kulikov; T. I. Batluk; A. A. Kuznetsova; N. I. Tereshchenko; S. K. Malyutina; Yu. P. Nikitin (Атеросклероз, 2015)
Myocardial electric instability, apparently , has a multigenic and multifactorial basis. It is interesting to examine of the association of the QTc interval with CC chemokine receptor 2 gene polymorphism (CCR2) and metabolic syndrome components. Survey data from a representative sample 831 men aged 25–64 out of a general population of Novosibirsk («MONICA» WHO project) were used. For genetic research by randomly were selected 393 people. The components of the metabolic syndrome (obesity, hypertension, hypertriglyceridemia and hypo-alpha-lipoproteinemia) were determined according to the WHO criteria. To calculate the corrected QTc interval Bazett formula has been used. The analysis in the multivariate linear regression model showed that the QTc interval was independently associated with 64V/64I(rs1799864) CCR2 gene polymorphism (p = 0.04) and hypertension (p = 0.0003).